PERUBAHAN SIFAT FISIK PISANG CAVENDISH SEGAR AKIBAT PENYIMPANAN DALAM SUHU RENDAH - Donowarti, Idiek; Kirnoprasetyo, Istiyono (Universitas Panca Marga, 2024)
Indonesia's banana exports have increased in line with the increasing demand for fresh fruits in the international market. Data from BPS shows that in 1993 Indonesia's banana exports only reached 1300 tons, but in 1994, 1995 and 1996 there were 33 092 tons, 55 317 tons and 94 107 tons of bananas with a value of 5 821 934, 8 637 427 and 17 356 737 USD, respectively. . As a perishable commodity, Indonesia's banana exports are faced with technical constraints in post-harvest handling to anticipate transportation needs that allow the fruit to survive raw during transportation with maintained quality. This study aims to determine the changes in the physical properties of fresh Cavendish bananas due to low temperature storage. This study is a Factorial experiment prepared by a Complete Random Design (RAL) consisting of two factors. Factor I is Storage in Low Temperature (KD) i.e. KD1 (stored at 13 Each is repeated 3 times. The observations made during the study included three stages, namely: the raw materials before storage, after storage, and after the bananas reached a color score of 6 (ripening at room temperature). Observations are made after 35 days of storage. The results showed that there were changes in physical properties in weight loss, flesh/skin ratio and fruit hardness)